2019
DOI: 10.1177/2056305119881691
|View full text |Cite
|
Sign up to set email alerts
|

Social Media, Interrupted: Users Recounting Temporary Disconnection on Instagram

Abstract: This article looks at the discourses of Instagram users about interrupting the use of social or digital media, through hashtags such as “socialmediadetox,” “offline,” or “disconnecttoreconnect.” We identified three predominant themes: posts announcing or recounting voluntary interruption, mostly as a positive experience associated to regaining control over time, social relationships, and their own well-being; others actively campaigning for this type of disconnection, attempting to convert others; and disconne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 32 publications
1
62
0
1
Order By: Relevance
“…This constant encouragement of continuous connectedness has raised concerns about users’ mental health and well-being, particularly when dealing with information overload (Andrejevic, 2013) or connection overload (LaRose et al, 2014). This has also spurred resistance movements such as digital detox (Sutton, 2017; Syvertsen and Enli, 2019) and temporary disconnection (Jorge, 2019). In spite of these punctual initiatives, what we generally have is the reinforcement of always-on connectedness and engaged, active attentiveness under the pressure that, at any time, something worthy of attention – something eventful – might happen, and that social media are the best available resource for us to keep track of this ongoing informational flux.…”
Section: Social Media Predictability and Continuous Connectednessmentioning
confidence: 99%
“…This constant encouragement of continuous connectedness has raised concerns about users’ mental health and well-being, particularly when dealing with information overload (Andrejevic, 2013) or connection overload (LaRose et al, 2014). This has also spurred resistance movements such as digital detox (Sutton, 2017; Syvertsen and Enli, 2019) and temporary disconnection (Jorge, 2019). In spite of these punctual initiatives, what we generally have is the reinforcement of always-on connectedness and engaged, active attentiveness under the pressure that, at any time, something worthy of attention – something eventful – might happen, and that social media are the best available resource for us to keep track of this ongoing informational flux.…”
Section: Social Media Predictability and Continuous Connectednessmentioning
confidence: 99%
“… 4 On the other hand, some statistics reveal that 42% of Facebook users in the United States have taken a break from checking the site for several weeks or more and 26% have removed the app from their mobile phones. 5 Moreover, several different studies showed that some users of well-known social media platforms are considering temporary disconnection from Instagram, 6 , 7 Facebook, 6 , 8 WeChat, 9 MySpace, 10 WhatsApp, 11 or Twitter. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, disconnection can be reinterpreted as a set of situated practices that do not refuse, but instead, complexify our everyday encounters with digital technologies. In order to do so, we also need to infuse politics onto disconnection (Fish, 2017; Jorge, 2019), decommodifying it and recasting it instead as a critique to digital capitalism. Disconnection could be situated within a broader frame of collective political responsibility aimed at producing social and political change, opening ‘new ways of imagining relations between technologies and freedoms, engagement and digitality and sociality and refusal’ (Kuntsman and Miyake, 2019: 2).…”
Section: Resultsmentioning
confidence: 99%